Late Glacial organic sediments in palaeogeographical reconstructions (cases from the Łódź region) - Dzieduszyńska, Danuta; Forysiak, Jacek (Bulletin of Geography. Physical Geography Series, 2015)
Late Glacial organic succession is recorded at the Żabieniec and Koźmin Las sites, in the Łódź region. A multiproxy approach provides a palaeogeographical assessment and yields a new insight into the old morainic area of the Polish Lowland. Additionally, the key profile Witów contributes in the reconstruction. It is demonstrated that the Late Glacial organic sediments of the Łódź region contain signs of environmental changes, starting from the first warming just after the Weichselian ice-sheet retreat from the Polish territory. Records at Żabieniec, apart from registering biotic and abiotic conditions which influenced functioning of a peatbog, provides information on the permafrost behaviour throughout the Late Glacial. At Koźmin Las, a unique discovery of the in situ riparian forest accompanied by organic sediments led to a high-resolution study of a series of events taking place on the floodplain during the Younger Dryas.